2019
DOI: 10.1007/s40573-019-00100-y
|View full text |Cite
|
Sign up to set email alerts
|

Konstruktion eines qualitativen Niveaumodells im fachdidaktischen Wissen von angehenden Physiklehrkräften

Abstract: Zusammenfassung Der vorliegenden Artikel zielt darauf ab, qualitative Fähigkeitsniveaus für das fachdidaktische Wissen angehender Physiklehrkräfte zu formulieren. Neben dem Fachwissen und dem pädagogischen Wissen stellt das fachdidaktische Wissen den zentralen Bereich des Professionswissens von Lehrkräften dar, da er sowohl für die Qualität des Unterrichts als auch für den Lernerfolg der Schülerinnen und Schüler entscheidend ist. Diese besondere Stellung des fachdidaktischen Wissens begründet das Interesse an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…For this purpose, proficiency levels are suited (Beaton & Allen, 1992;Lok et al, 2016). In this study, we confirmed the results of the initial study of Schiering et al (2019) by using more than double the number of pre-service teachers as the foundation of the proficiency levels. Analyzing the items close to the level thresholds revealed that knowledge at lower proficiency can be characterized as remembering content unspecific and factual knowledge (e.g., knowing typical characteristics of inquiry-based teaching), whereas pPCK at higher proficiency encompasses more contentspecific strategies to structure and elaborate lessons (e.g., being able to justify extracurricular activities in light of students' learning).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…For this purpose, proficiency levels are suited (Beaton & Allen, 1992;Lok et al, 2016). In this study, we confirmed the results of the initial study of Schiering et al (2019) by using more than double the number of pre-service teachers as the foundation of the proficiency levels. Analyzing the items close to the level thresholds revealed that knowledge at lower proficiency can be characterized as remembering content unspecific and factual knowledge (e.g., knowing typical characteristics of inquiry-based teaching), whereas pPCK at higher proficiency encompasses more contentspecific strategies to structure and elaborate lessons (e.g., being able to justify extracurricular activities in light of students' learning).…”
Section: Discussionsupporting
confidence: 75%
“…These discrete proficiency levels then provide descriptions about the actual knowledge associated with different scale locations (Mullis & Fishbein, 2020) and, thus, allow for an interpretation of an otherwise abstract numerical achievement scale (James & Rossiter, 2018). For pre-service physics teachers' pPCK, we concluded in an initial study (see Schiering et al, 2019) that pre-service physics teachers' pPCK at lower levels can mostly refer to factual knowledge, such as knowing about possible misconceptions. Higher levels of pre-service physics teachers' pPCK were associated with reflective skills, such as evaluating instructional strategies (Schiering et al, 2019).…”
Section: Development Of Science Teachers' Ppckmentioning
confidence: 99%
See 2 more Smart Citations